1993
DOI: 10.1161/01.hyp.22.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Flow regulation of vascular tone. Its sensitivity to changes in sodium and calcium.

Abstract: Our hypothesis is that flow-through hydraulic drag or shear stresses the extracellular elements in the vascular wall. When the endothelium is intact, this results in the release of endothelium-derived relaxing factor and other substances, eg, prostanoids, from the endothelium. As in some reports, after inhibition of nitric oxide synthase, flow effects are still observed although diminished; the shear effect is extended mechanically to the subendothelial tissues. Shear causes conformational changes in the glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…The mechanism that underlies the apparent salt-dependent decrease in microvascular Cu/Zn SOD activity is unclear. In HS rats, plasma sodium levels are not elevated for more than 2–3 days [50, 51], but a resulting sodium accumulation in vessel walls may lead to a more sustained change in the endothelial microenvironment [52]. Since most vascular wall sodium is extracellular and bound to membrane-associated glycosaminoglycans [53], increased sodium binding could influence endothelial cell function by altering the charge distribution or some other property of endothelial glycocalyx [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism that underlies the apparent salt-dependent decrease in microvascular Cu/Zn SOD activity is unclear. In HS rats, plasma sodium levels are not elevated for more than 2–3 days [50, 51], but a resulting sodium accumulation in vessel walls may lead to a more sustained change in the endothelial microenvironment [52]. Since most vascular wall sodium is extracellular and bound to membrane-associated glycosaminoglycans [53], increased sodium binding could influence endothelial cell function by altering the charge distribution or some other property of endothelial glycocalyx [52].…”
Section: Discussionmentioning
confidence: 99%
“…In HS rats, plasma sodium levels are not elevated for more than 2–3 days [50, 51], but a resulting sodium accumulation in vessel walls may lead to a more sustained change in the endothelial microenvironment [52]. Since most vascular wall sodium is extracellular and bound to membrane-associated glycosaminoglycans [53], increased sodium binding could influence endothelial cell function by altering the charge distribution or some other property of endothelial glycocalyx [52]. Although speculative, such changes could directly influence Cu/Zn SOD activity, since the Cu/Zn SOD that is thought to be most important for regulating NO bioavailability in the vasculature is an extracellular glycoprotein that mainly exists bound to the endothelial cell glycocalyx [54].…”
Section: Discussionmentioning
confidence: 99%
“…10 -13 Previous studies have shown a specific sensitivity of flow-induced dilation and myogenic tone to small changes in extracellular sodium concentration. 1,14 We hypothesized that flow-induced dilation and myogenic tone might be selectively influenced by high salt intake. We used mesenteric resistance arteries from spontaneously hypertensive rats (SHR) submitted to high dietary salt intake.…”
mentioning
confidence: 99%
“…Flow has been described as a stimulus for the endothelial cells to liberate vasodilator substances (9-11). On the other hand, the increase in pressure stretches the endothelial layer, inducing the release of endotheliumderived contraction factor (EDCF) (9,10,12). In our protocol, the increase in pressure may release endothelial EDCF that acts synergistically with PE by potentiating the pressure increment produced by flow.…”
Section: Discussionmentioning
confidence: 95%